Blackspot analysis of road traffic crashes in Surabaya - Manyar Toll Road, East Java - Hartatik, Nurani; Prasetijo, Joewono; Muslihati, Atqiya (2021)
Traffic crashes are one of the problems that cannot be prevented, especially on toll roads. Knowing the crash element, including crash number, type, factor, and fatality, could lead the investigation to set crash solving and prevention by finding the blackspot point. Surabaya-Manyar toll roads were reported as crash-prone locations, with 149 crashes from 2014-2018. This research concerns the impact on a specific period obtained by PT. Margabumi Matrajaya was ranging from 2014-2018 at Surabaya-Manyar toll road. The objectives aim to analyze the crash element using submitted data from PT. Margabumi Matrajaya to find the blackspot at each line. The collected data were the primary data from field observation and documentation and secondary data, consisting of crash data, road length, time of the crash, what types of vehicles were involved in the crash, and wound victim data. The locations of crash-prone points (Blackspots) on the Surabaya - Manyar Toll road are as follows: The locations of crash-prone points (Blackspots) on the Surabaya Toll road - Manyar line mostly occurred at Km 9 + 925 - 16 + 400 mostly in 2018, on the Romokalisari - Kebomas section, and for Manyar - Surabaya line, occurred at Km 3 + 500 - 0 + 000 mostly in 2016, on the Tandes - Dupak section. Therefore, to decrease the crash number in Surabaya - Manyar toll road, PT. Margabumi Matrajaya should add traffic sign as blackspot area, speed trap, warning sign like slippery road ahead warning, crossroad, and merging traffic.